Real estate acquisition barrier and its impact on urban development projects" Study Area: Infrastructure project in the capital Baghdad (North East Sewage Line project AL khansaa) - Ali, Jalal Atheeb; Othman, Areaj Khairi (Journal of Planner and Development, 2020)
The increase the rates of natural growth, urbanization and continuous migration, this has generated constant pressure and, as a result, the capital city of Baghdad faces a number of challenges related to its urban environment, including the challenge of acquiring real estate.  and this research examines the impact of these holdings, representing the main base from which the various projects originate Urban in all areas (economic, social, and recreational). this leads us to the research problem of the obstacles that arise during the process of acquiring real estate to carry out development projects, and to achieve the objectives of research, namely (work to create a regulatory methodology (legal- Planning) for the acquisition of real estate, for easy handling and inventory of associated problems and constraints). the city needs to overcome these barriers to help select the best solutions with more sustainable results, Finally, based on the concepts reached in the theoretical framework and the results Analysis of the study area in the chapter of the practical framework.  and in order to benefit from research to solve the research problem, the research came out with a number of conclusions and recommendations.